Implementasi Sistem Premi Panen dan Dampaknya terhadap Kinerja dan Kepuasan Kerja Karyawan Panen PT Perkebunan Nusantara V Kebun Sei Buatan Pekanbaru - TARIGAN, PIUS BELO; BUDIASA, I WAYAN; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p47, 2023)
Implementation of the Harvest Premium System and its Impact on the Performance and Job Satisfaction of Harvest Employees at PT Perkebunan Nusantara V Kebun Sei Buatan Pekanbaru Harvest premium is the income earned by harvest employees if the harvested production has reached the wholesale basis set by the company. The harvest premium system at PT Perkebunan Nusantara V Kebun Sei Buatan uses a weight system. The purpose of this study was to analyze how the influence of harvest premiums on the performance and job satisfaction of harvest employees at PT Perkebunan Nusantara V Kebun Sei Buatan Pekanbaru. The sample in this study was determined based on non-probability using the saturated sampling method (census), where all members of the population were sampled in this study as many as 68 samples. This research was conducted by means of interviews and documentation as well as questionnaires where the variables were measured using a Likert scale instrument. Data were analyzed using simple linear regression analysis with the help of SPSS. The results showed that the harvest premium had an effect on the performance and job satisfaction of harvest employees. Suggestions from the results of this study to employees of PT Perkebunan Nusantara V Kebun Sei Buatan Pekanbaru is to optimize the sources of labor in the family and carry out harvesting orderly in order to improve harvest performance.